Commercial Internet Publishing–The Practicalities - Nash, John C.; Nash, Mary M. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper is an update of our 1995 presentation, Internet Book Publishing–a case study, where we reported our experience in publishing Scientific Computing with PCs using File Transfer Protocol (FTP) under a shareware model. While this experience was useful, we believe "begware" to be an impractical mechanism for commercially viable publishing. The present discussion will consider the costs of Internet publishing, approaches to its implementation, decisions regarding the packaging of products, marketing. . .